Implementasi Pelatihan Pemanfaatan TIK Bagi Guru Sekolah Binaan KB Sya’roniyah Purwogondo - Muhammad Nofan Zulfahmi (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Information and Communication Technology (ICT) is one of the important aspects in online learning for human resources (HR) in the target schools, namely teachers. Management of ICT needs for human resources of teachers in a fostered school (sekolah binaan) can be done by conducting a training. The purpose of this study is to describe the training process carried out by the PGPAUD FTIK Unisnu Jepara school fostering team and the effectiveness of the training activities. This type of research is descriptive with a qualitative approach. Research informants came from KB Sya'roniyah teachers, with 12 people. The types of data used are primary data and secondary data. while, the data collection methods are observation, interviews and documentation. Data analysis technique in this research is descriptive analysis with data testing method using triangulation. The results of the study show that the training process for teachers of the Sya'roniyah KB Purwogondo schools had several stages, those are needs analysis, training objectives, and determining the training program material. Evaluation is carried out to verify the effectiveness of the training. Based on the results of the evaluation of the training activities showed a positive response from the training participants. The ICT utilization training attended by the Sya'roniyah KB teacher was effective because the creativity of the teachers in using ICT after attending the training had increased and the level of parental complaints against online learning had also decreased.